2016
DOI: 10.1016/j.pmedr.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood factors and six-month weight change among overweight individuals in a weight loss intervention

Abstract: The purpose of this study was to examine the neighborhood environment and the association with weight change among overweight/obese individuals in the first six months of a 12-month weight loss intervention, EMPOWER, from 2011 to 2015. Measures of the neighborhood environment included neighborhood racial composition, neighborhood income, and neighborhood food retail stores density (e.g., grocery stores). Weight was measured at baseline and 6 months and calculated as the percent weight change from baseline to 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 24 publications
(26 reference statements)
0
21
0
Order By: Relevance
“…Some more recent studies are longitudinal, examining the long‐term effects of environmental factors on weight and related behaviors, or alternatively among individuals who move from one environment to another or among those otherwise exposed to environmental changes (e.g., pedestrian infrastructure improvements, opening new food stores) . The ADOPT environmental domain subgroup was only aware of a limited number of published reports that examine the association of environmental factors with weight‐loss or maintenance among adult weight‐management trial participants (e.g., Mendez et al and Zenk et al ).…”
Section: Identifying High‐priority Constructs and Measures For Enviromentioning
confidence: 99%
See 1 more Smart Citation
“…Some more recent studies are longitudinal, examining the long‐term effects of environmental factors on weight and related behaviors, or alternatively among individuals who move from one environment to another or among those otherwise exposed to environmental changes (e.g., pedestrian infrastructure improvements, opening new food stores) . The ADOPT environmental domain subgroup was only aware of a limited number of published reports that examine the association of environmental factors with weight‐loss or maintenance among adult weight‐management trial participants (e.g., Mendez et al and Zenk et al ).…”
Section: Identifying High‐priority Constructs and Measures For Enviromentioning
confidence: 99%
“…As with other environmental factors, current data are limited on the impact of neighborhood‐level socioeconomic characteristics on adult weight loss or weight‐loss maintenance . However, extensive observational data support inclusion of neighborhood deprivation as an ADOPT environmental domain subgroup construct.…”
Section: Environmental Constructs and Corresponding Measures Recommenmentioning
confidence: 99%
“…They consist of elements across the physical, social, built, and economic environment that jointly impact access to resources and ability to engage in healthy behaviors. However, existing work on neighborhood environments and cardiometabolic pregnancy outcomes largely investigates neighborhood characteristics separately . Studies investigating neighborhood socioeconomic deprivation largely find no association with excessive GWG and mixed associations for GDM .…”
Section: Introductionmentioning
confidence: 99%
“…However, existing work on neighborhood environments and cardiometabolic pregnancy outcomes largely investigates neighborhood characteristics separately . Studies investigating neighborhood socioeconomic deprivation largely find no association with excessive GWG and mixed associations for GDM . Studies investigating neighborhood social environment , including presence of social spaces, physical incivilities, ethnic enclaves, and community violence, find associations with excessive GWG but not with GDM .…”
Section: Introductionmentioning
confidence: 99%
“…Mendez et al. (), in a secondary analysis of data from a study evaluating triggers for lapses or relapse after intentional weight loss, found no relationship between census tract density of grocery stores/supermarkets or restaurants and percent weight loss at 6 months among 127 overweight and obese adults participating in a group‐delivered intervention. The study is quite different from ours.…”
Section: Discussionmentioning
confidence: 99%